Assessing the Integration and Differentiation of Logistical Processes in Healthcare Settings - Ahmed Gh Alkordi Alghamdi; Ali Suwailem Alotaibi; Manal Naser bin sunbil; Mehinat Alobaidan; Sultan Jadi Alharbi; Fahad Eid Alharbi; Khalid Obaid Alharbi; Abdulrahman Khalid Alaqeel; Sultan Abdulaziz Howaimal; Hammad Alaiyt M Alanazi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article explores the concepts of integration and differentiation within hospital logistical systems through the lens of social network analysis. As healthcare organizations face increasing pressure to improve efficiency while maintaining quality care, understanding the structural dynamics of hospital logistics becomes crucial. This research examines how differentiated hospital departments and functions achieve integration to create effective patient flows and resource allocation. Using social network analysis as a methodological framework, the article identifies key logistical parameters and explores how network structures reflect the balance between specialized functions and coordinated operations. The findings suggest that strategic approaches to integration can optimize hospital performance while respecting necessary functional differentiation, ultimately contributing to more resilient healthcare delivery systems.